Development of Physics Pocketbook Mobile on Android (Phy-pockemon) to Address Scientific Literacy on Energy Source Concepts - Muhamad Zayin El-hak; Rudi Haryadi; Ganesha Antarnusa (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to determine the feasibility of developing a physics pocketbook mobile on Android (Phy-pockemon) to address scientific literacy skills in energy source material. The research method used is Research and Development (RD) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The result of the developed media is the Phy-Pckemon application. Through expert validation referring to the educational information and communication technology center, subject matter expert validation carried out by three validators obtained a percentage value of 95% with a very feasible category. Media expert validation received a percentage value of 94% with a possible category, while based on trials limited to the Technological Acceptance Model (TAM) evaluation, which was conducted on 20 class XII students at one of the Islamic senior high school in Indonesia, an average response percentage of 93% was obtained with a very decent category. The results show that using Phy-Pockemon to address scientific literacy skills in energy sources is appropriate for use in learning.